Lafora disease presented with multiple seizure - Nayeem, Rahatun; Nayeem, Abu; Mandol, Gurudas; Salsabil, Tasmia; Shams, Sifat; Islam, Md Nowfel; Mohammad, Quazi Deen (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Among different types of Progressive Myoclonic Epilepsy (PME), Lafora disease is an autosomal recessive disorder, with age of onset 6-19 years. It is quickly progressive, and death occurs within 10 years. It is a glycogen metabolism disorder characterized by the presence of inclusion bodies, known as Lafora bodies within the cytoplasm of the skin, liver, breast and muscle. Lafora disease presents as a neurodegenerative disorder with difficult to control seizures mostly like progressive myoclonic epilepsy. But the disease may also present with multiple types of seizures like generalized tonic clonic, focal with secondary generalization, myoclonic, absence etc. Patient may also present with psychomotor regression with ataxia, dysarthria, dementia, visual hallucination etc. Electroencephalogram (EEG) shows generalized spike/ polyspikes and waves with photosensitivity and background slowing. Diagnosis is further confirmed by presence of inclusion bodies (Lafora body) with typical histological findings on skin biopsy and genetic testing. Here we present a case of Lafora disease that presented with progressive myoclonic epilepsy and generalized tonic clonic seizure. We took proper history, did meticulous clinical examination and investigated her at our institute. We confirmed the patient having Lafora disease with typical histological findings that is presence of Lafora body on skin biopsy taken from axilla. Then treatment was given to the patient accordingly and proper counseling was done about the disease and its prognosis. J Bangladesh Coll Phys Surg 2023; 41(4): 329-333